Passiflora incarnata L., herba, in benzodiazepine tapering: long-term safety and efficacy in a real-world setting - Carminati, Matteo; Tondello, Mattia; Zanardi, Raffaella (Frontiers in Psychiatry, 2024)
Introduction Chronic and inappropriate benzodiazepine (BDZ) prescription and intake represent an important health and social concern worldwide. The aim of our study was to investigate the safety and efficacy of P. incarnata L., herba in reducing BDZ misuse in a real-world population of depressed and anxious patients in a long-term treatment with BDZs. Methods Over an 18-month period (from July 2021 to December 2022), we previously conducted a retrospective and naturalistic study on euthymic outpatients with a diagnosis of anxiety or depression and chronically taking BDZs. In this study we contacted patients 12 months after their enrollment in the previous study to assess their disease status and their BDZs and P. incarnata intake. Results Our findings support the effectiveness of a dry extract of P. incarnata L., herba, as an add-on treatment during BDZ tapering in patients with anxiety or depression. We confirmed this effect to be sustained over time, and P. incarnata showed to be easily discontinued with no rebound, withdrawal or psychological dependence effect. The absence of side effects and adverse events confirmed the safety of P. incarnata in a real-world population. Personality disorders confirmed to be a relevant risk factor for maintaining addictive behavior, even when symptoms associated to withdrawal seem to be not particularly relevant. Discussion We confirmed the possible effectiveness of P. incarnata as an add-on treatment in BDZ reduction. Further studies may be helpful to better investigate the promising properties of P. incarnata in the management of relevant clinical issues, such as anxiety disorders and addiction, that are classically known to benefit from GABAergic treatments.